2018
DOI: 10.1111/aos.13907
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of treatment of hyposecretory dry eye with platelet‐rich plasma

Abstract: Objective: To evaluate and compare the symptomatology and clinical findings in hyposecretory dry eye of the treatment with platelet-rich plasma (PRP) and artificial tears of sodium hyaluronate (SH). Methods: Blind single-centre prospective comparative randomized study including 83 patients with hyposecretory dry eye and mean age of 64.0 years. Two groups were differentiated depending on the treatment applied: 44 patients treated with PRP (PRP group), and 39 patients treated with artificial tears of SH (SH grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Similar results were obtained in 25 NK patients treated by Wróbel-Dudzinska et al with PRP eye drops, with complete healing of the corneal ulcer observed in 80% of patients, while improved symptoms and visual acuity observed in all of them [118]. In a randomized clinical trial, Garcia-Conca et al compared PRP eye drops with tear substitutes in patients with hyposecretory DED [119]. Patients treated with PRP showed a significantly higher improvement in symptoms, visual acuity, conjunctival hyperaemia, corneal and conjunctival staining, Schirmer test, and tear osmolarity [119].…”
Section: Platelet Derived Eye Dropsmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar results were obtained in 25 NK patients treated by Wróbel-Dudzinska et al with PRP eye drops, with complete healing of the corneal ulcer observed in 80% of patients, while improved symptoms and visual acuity observed in all of them [118]. In a randomized clinical trial, Garcia-Conca et al compared PRP eye drops with tear substitutes in patients with hyposecretory DED [119]. Patients treated with PRP showed a significantly higher improvement in symptoms, visual acuity, conjunctival hyperaemia, corneal and conjunctival staining, Schirmer test, and tear osmolarity [119].…”
Section: Platelet Derived Eye Dropsmentioning
confidence: 52%
“…In a randomized clinical trial, Garcia-Conca et al compared PRP eye drops with tear substitutes in patients with hyposecretory DED [119]. Patients treated with PRP showed a significantly higher improvement in symptoms, visual acuity, conjunctival hyperaemia, corneal and conjunctival staining, Schirmer test, and tear osmolarity [119].…”
Section: Platelet Derived Eye Dropsmentioning
confidence: 99%
“…Among all studies treating dry eye diseases (DED), Avila et al 27 was designated at clinical evidence level II, and Garcia-Conca et al 28 at clinical level III. Both studies included a comparison group and used PRP eye drops.…”
Section: Primary and Secondary Dry Eye Diseasesmentioning
confidence: 99%
“…Pezzotta et al investigated the efficacy and safety of long-term continuous treatment with autologous platelet lysate drops in oGvHD patients with a DED score of 2-3 which had symptoms refractory to topical conventional therapy (Pezzotta et al, 2017). García-Conca et al claimed that treatment of hyposecretory DED with PRP induced a significantly more positive effect on the signs and symptoms of DED than did sodium hyaluronate, particularly in moderate and severe cases (García-Conca et al, 2019). Subsequently, Arslan et al obtained promising preliminary clinical results in a study investigating the use of subtenon injection of aPRP to treat patients with RP in terms of significant improvements in VF, mfERG values, and MP (Arslan et al, 2018).…”
Section: Bioactive Natural Products In Romentioning
confidence: 99%